Pediatric herpes zoster: should I be concerned for immunodeficiency? A review - Steven Zhang; Vy H. D. Kim; Eyal Grunebaum (Frontiers in Pediatrics)
Herpes zoster (HZ), caused by reactivation of varicella-zoster virus (VZV), is an uncommon cause of rash in pediatrics, which can lead to concerns of an underlying immunodeficiency. We reviewed studies on HZ in pediatric patients. The diagnosis of HZ can usually be established based on clinical and epidemiological features. HZ is associated with T-cell immune defects that can be secondary to infections with HIV, tuberculosis, and other pathogens, as well as conditions such as diabetes, malnutrition, cancer, or primary immunodeficiency. Important clinical clues indicating that HZ is due to an underlying immunodeficiency include recurrent HZ during a short period; disseminated HZ; new lesions more than a week after presentation; prolonged course despite antiviral medications; a history of recurrent, invasive, or prolonged infections by other pathogens; and a family history of immunodeficiency or consanguinity. Reassuring features include exposure to VZV prior to 1 year of age or a compromised or incomplete VZV vaccination schedule. Initial laboratory analysis may include confirmation of normal newborn screening for profound T-cell immunodeficiency; a complete blood count with differential, quantitative serum immunoglobulins; lymphocyte subset analysis; and the presence of IgG to VZV. In children previously vaccinated for VZV, the possibility of vaccine-type HZ needs to be considered. In conclusion, isolated and uncomplicated childhood HZ is unlikely to be the sole harbinger of an underlying immunodeficiency. Therefore, most children with HZ can be adequately diagnosed through medical history and readily available laboratory evaluations. The presence of concerning clinical or laboratory features should prompt an evaluation by an experienced specialist.